Sistem Informasi Pemesanan Gor Badminton Dengan Payment Midtrans Di Desa Waru: Sistem Informasi Pemesanan GOR Badminton Dengan Payment Midtrans Di Desa Waru - Saputra, Rafi'i Dwi; Susanto, Rudi; Hartanti, Dwi (Universitas Islam Syekh Yusuf, 2023)
The Waru Village GOR has 3 fields and the scheduling is divided into 4 sessions. Customers who want to order GOR must come directly. This is considered less effective. Apart from that, there are schedule pile-ups. The rental money from customers is entrusted to the Gor guard, then the Gor manager takes the rent money at least once every three weeks. The aim of this research is to build a badminton game ordering system to make building management easier, in terms of ordering games and also payments that can be made online, so that payments made can be received directly by the building manager. This research uses 2 methods, namely the first method is a data collection method which includes observations and interviews, the second is a system development method using waterfall which has 5 stages, namely Requirement Analysis, System and software Design, Implementation and Unit Testing, Integration and System Testing, and Operation and Maintenance. The final result of this system is a badminton sports ordering system with payments that are integrated with Midtrans. This system can help admins in managing sports schedules, printing reports and payments which are directly received by the admin. Apart from that, admins can also share information related to sports with customers through the system. Customers are also helped by this system, namely customers no longer need to come to the gym directly. Customers can make field orders through the system and make payments through a system that is integrated with MidTrans. Customers can choose which bank they make payments with.